Systematic Mapping of the Researchers’ Training as an Element of Reflective Analysis in Educational Training Environments (2017-2021) - Múzquiz Flores, Marlene (2022)
The training of educational researchers represents a complex process due to the nature of educational research itself, for it implies different practices and actors. The foregoing includes research cores integrated under their training, which, in addition to gathering skills and abilities, are specified in an academic task that promotes and facilitates the subject in training the access and development of knowledge, interaction with the social environment, development of skills, attitudes, and habits that the same research practice itself requires and demands. Thus, this paper aims to analyze the empirical evidence published between January 2017 and October 2021 about the training of researchers as an element of reflection in educational training environments, with a focus on distinguishing what research has been carried out, what processes have addressed, and their contributions for future studies. The researchers chose the systematic literature mapping method, applied inclusion and exclusion criteria to the articles located in the SCOPUS and Web of Science (WoS) databases, and delimited 100 articles as the object of study. Regarding the results, they portray the types of methodologies that were applied, the most cited articles, the journals where they were published, the geographical distribution of the authors, the contexts of application, and the addressed topics. Hence, the article adds value to the field of research, as it identified the advances, places, and contexts, as well as the challenges and opportunities for training and research.